Goal Detection in Soccer Video: Role-Based Events Detection Approach - Farshad Bayat; Mohammad Shahram Moin; Farhad Bayat (Institute of Advanced Engineering and Science, 2014)
Soccer video processing and analysis to find critical events such as occurrences of goal event have been one of the important issues and topics of active researches in recent years. In this paper, a new role-based framework is proposed for goal event detection in which the semantic structure of soccer game is used. Usually after a goal scene, the audiences’ and reporters’ sound intensity is increased, ball is sent back to the center and the camera may: zoom on Player, show audiences’ delighting, repeat the goal scene or display a combination of them. Thus, the occurrence of goal event will be detectable by analysis of sequences of above roles. The proposed framework in this paper consists of four main procedures: 1- detection of game’s critical events by using audio channel, 2- detection of shot boundary and shots classification, 3- selection of candidate events according to the type of shot and existence of goalmouth in the shot, 4- detection of restarting the game from the center of the field. A new method for shot classification is also presented in this framework. Finally, by applying the proposed method it was shown that the goal events detection has a good accuracy and the percentage of detection failure is also very low.DOI:http://dx.doi.org/10.11591/ijece.v4i6.6377